The Impact of COVID-19 on Psychological and Social Stigma for Indonesian Nurses: A Cross-Sectional Survey - Mustikasari, Mustikasari; Fadhillah, Harif; Sunadi, Apri; Nursalam, Nursalam; Mediawati, Ati Surya; Adam, Muhammad (Frontiers in Psychiatry, 2022)
Introduction Nurses are on the front line and are at high risk of experiencing a mental health crisis during the pandemic due to the psychological impact and stigma. The aim of this study was to identify the role of psychological status and social stigma in anxiety, fear, depression, and mental health crises during the pandemic. Materials and Methods A cross-sectional design during December 2020–August 2021. A total of 2,156 nurses who work in health facilities, either hospitals, or communities based on the criteria of nurses who interact directly with COVID-19 patients, work at least 3 months, age 20–54 years, are literate, have internet access, and have the ability to access the electronic form. The eligible participants filled in online questionnaires that were sent to them via WhatsApp. Data were analyzed using Spearman rho correlation test with statistically significant p value < 0.05. Results A total of 2,156 respondents responded to the questionnaire, and the response rate was 100%. The psychological status of nurses was 78.4% moderate, 18.5% experienced social stigma, 44.0% showed an anxiety response, 53.5% fear, 64.5% depression in the very severe category, and 63.5% fell into a mental health crisis. The results of the inferential analysis showed that all P < 0.05 which indicated that psychological status and social stigma had a significant relationship with anxiety, fear, depression, and mental health crisis in nurses. Conclusion The psychological status and social stigma experienced by nurses during the COVID-19 pandemic indicate a bad situation and lead to a mental health emergency crisis.